FACIAL NERVE PARALYSIS AS A COMPLICATION OF ACUTE OTITIS MEDIA IN CHILDREN: A CASE REPORT AND LITERATURE REVIEW - Zdravković, Đorđe; Zlatković , Slađan (Sanamed, 2025)
Introduction: The facial nerve controls facial expression, and its dysfunction causes facial asymmetry and reduced mimic function. Facial nerve paralysis is significantly less common in children compared to adults. Children under the age of 10 are estimated to have an incidence rate of approximately 3 per 100,000 per year. The leading cause of facial paralysis in the pediatric population is idiopathic (Bell’s palsy), similar to that in adults. In cases where the cause is not idiopathic, infections accompanied by trauma and congenital anomalies are the most frequent etiological factors of facial nerve paralysis in children. This condition is most often attributed to nerve edema and subsequent compression within the bony fallopian canal.Case Report: This report presents a case of peripheral facial nerve paralysis as an extracranial complication of acute otitis media in a 2-year-old child. It also includes a literature review focusing on recent diagnostic protocols, evaluation, and therapeutic approaches.Conclusion: As demonstrated in our case, the prognosis for facial nerve paralysis associated with acute otitis media (AOM) was generally good after appropriate therapy. Recovery from facial paralysis usually occurs within three months. This report delineates a rare complication of AOM in children. Timely recognition and appropriate therapy are crucial to achieve good outcomes.
Keywords: facial nerve paralysis; acute otitis media; complications